Kesiapan Orang Tua Anak Usia Sekolah (7-11 Tahun) Dalam Menerima Vaksinasi COVID-19 - Made Indra Ayu Astarini; Ira Ayu Maryuti; Johanes Sujitno (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The purpose of this study was to explain the relationship between perception with the readiness of parents of school-age children (7-11) years to receive COVID-19 vaccination. Methods:  The research design is correlation with cross sectional approach. Subjects were parents of 275 school-age children. Sampling technique using consecutive sampling. The independent variables were parents' perception of COVID-19 vaccination. The dependent variable is the readiness of parents. Data analysis using Spearman Rho test with α= 0.05 (ρ<α).Results:  The majority of respondents are ready to give COVID-19 vaccination as many as 241 people (88%). The majority of parents' perceptions of COVID-19 vaccination were good, and related to the readiness of parents to give COVID-19 vaccination (ρ=0.001). Conclusion:  Perception shapes the attitudes of parents. A good perception can form a positive attitude to be ready to receive a COVID-19 vaccination